Implementing a Domestic Violence Screening Program. Issue 3 (May 2015) - Day, Suzanne; Fox, Jolene; Majercik, Sarah; Redmond, Floresha K.; Pugh, Mary; Bledsoe, Joseph
<x xml:space="preserve">Abstract</x> The purpose of this study was to design and implement a domestic violence (DV) screening protocol. Trauma patients meeting inclusion criteria (hospitalized > 48 hours) were given a four question DV screen. If abuse was found, a comprehensive DV questionnaire followed. Barriers to screening and results were recorded. Compliance during the pilot test showed 23 of 157 (14.6%) admitted patients were screened. In the implementation year, 446 of 721 (61.9%) were screened. During the 10-month follow-up, 499 of 619 (80.6%) patients were screened. Lack of social work resources was the primary barrier to screening, but compliance increased and was maintained after the study period.